Silicon by modulating the antioxidant defense system reduces the need for water and potassium: a review - Ferreira, Patrícia Messias; Prado, Renato de Mello (Frontiers in Plant Physiology, 2025)
Potassium (K) deficiency in soils is common across various regions of the world, a problem exacerbated by the progression of drought due to climate change. A sustainable strategy to increase plant tolerance to drought involves the use of silicon (Si) and/or K; however, the biochemical mechanisms underlying this relationship require further elucidation. The objective of this review is to discuss the relevance of drought and nutritional deficiency to oxidative damage in crops, as well as the role of Si and K in the antioxidant defense system to enhance water use efficiency, including future research perspectives on this topic. This article examines the biochemical mechanisms involved in the interaction between Si, K, and the plant antioxidant system, emphasizing their potential to improve productivity with reduced water consumption and to mitigate challenges posed by climate change. The application of Si via fertigation has proven effective in increasing water use efficiency and modulating physiological processes, thereby promoting nutritional balance and antioxidant protection in different crops. The antioxidant effects of Si observed in field trials further reinforce its importance in enhancing physiological and nutritional responses to stress conditions in crops. Efficient Si fertigation may reduce the optimal Si rates compared to bulk applications in rainfed systems; however, it may also increase the risk of Si leaching, underscoring the need for additional research. The synergy between Si and K enhances water use efficiency by stabilizing metabolism and increasing plant resilience under adverse conditions. Future perspectives point to the optimization of Si and K fertigation as a promising strategy for sustainable agriculture, particularly in regions with water scarcity and nutrient deficiencies. The use of Si may also reduce the optimal irrigation requirements for crops without compromising yield, representing a viable alternative for irrigated agriculture that warrants further investigation in different cropping systems.